When Drotaverine (No-spa) Injected in to the Perivascular Tissues of Internal Mammary Artery (IMA) Relives the Peri-operative Vascular Spasm and Increases the Blood Flow in IMA When Used as a Pedicle Graft in CABG (Medical Forum Monthly, 2024)
Objective: To compare two groups of patients submitted to different modes of delivery of Drotaverine and its effect on internal mammary artery spasm during Coronary artery bypass grafting at The National Institute of Cardiovascular Diseases, Karachi.Study Design: Experimental study.Place and Duration of Study: This study was carried out at the National Institute of Cardiovascular Diseases Karachi from 1stJan 2013 to 31st December 2013.Materials and Methods: Data was analyzed from one hundred patients who underwent CABG at our institute. They were divided into two groups: Group 1 consisted of 50 patients in which Drotaverine (No-Spa) was sprayed topically over the IMA: Group 2 also consisted of 50 patients in which Drotaverine (No-Spa) was injected with blunt needle in the perivascular tissue of IMA.Results: After Drotaverine application, the mean blood flow were significantly low in Group I was 117.2 ±4.87 ml/min as compared to Group II which was 136.2 ±7.11 ml/min (p<0.01).Conclusion: Result of our study suggests ; Drotaverine injected perivascularly better relieves spasm of internal mammary artery and increases the blood flow .